2013
DOI: 10.1073/pnas.1303035110
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of recombination hotspot scanning during double-stranded DNA break resection

Abstract: Double-stranded DNA break repair by homologous recombination is initiated by resection of free DNA ends to produce a 3′-ssDNA overhang. In bacteria, this reaction is catalyzed by helicase-nuclease complexes such as AddAB in a manner regulated by specific recombination hotspot sequences called Crossover hotspot instigator (Chi). We have used magnetic tweezers to investigate the dynamics of AddAB translocation and hotspot scanning during double-stranded DNA break resection. AddAB was prone to stochastic pausing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 41 publications
3
61
1
1
Order By: Relevance
“…As such, it degrades DNA ends until it recognizes a Chi sequence, when it stops degrading the 3′ strand but continues unwinding and degrading the 5′ strand, thereby creating a ssDNA overhang, which can be further processed to repair the DNA. This has recently been demonstrated at the single molecule level using magnetic tweezers [109]. In this study the authors observed pausing at Chi and Chi-like sequences and therefore propose a model for Chi recognition, whereby the enzyme pauses and undergoes a multistep conformational change involving the extrusion of a ssDNA loop, before resuming translocation after the Chi site [109].…”
Section: Manipulation - Taking Hold Of the Problemmentioning
confidence: 82%
See 2 more Smart Citations
“…As such, it degrades DNA ends until it recognizes a Chi sequence, when it stops degrading the 3′ strand but continues unwinding and degrading the 5′ strand, thereby creating a ssDNA overhang, which can be further processed to repair the DNA. This has recently been demonstrated at the single molecule level using magnetic tweezers [109]. In this study the authors observed pausing at Chi and Chi-like sequences and therefore propose a model for Chi recognition, whereby the enzyme pauses and undergoes a multistep conformational change involving the extrusion of a ssDNA loop, before resuming translocation after the Chi site [109].…”
Section: Manipulation - Taking Hold Of the Problemmentioning
confidence: 82%
“…Magnetic tweezers have been used to study topoisomerases [104], polymerases [105], restriction enzymes [64,106] and helicases involved in DNA repair [107109] amongst others. One such study investigated UvrD unwinding rate, lifetime, and base pairs unwound.…”
Section: Manipulation - Taking Hold Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The quoted distances in base pairs were corrected using the value given by the worm-like chain model of rise per base pair of dsDNA at a given force. The unwinding rate was calculated by using the derivative of the smoothed data at 3 Hz in order to separate movement from pausing events (23).…”
Section: Magnetic Tweezers Translocation Assaymentioning
confidence: 99%
“…We used a home-made magnetic tweezers setup similar in design to that described in (58,59) and detailed in (60). In brief, images of 1 μm superparamagnetic beads tethered to the surface of a glass slide by DNA constructs are acquired with a 100x oil immersion objective and a CCD camera.…”
Section: Instrument and Samplesmentioning
confidence: 99%